Peningkatan Kemampuan Komunikasi Matematis dan Kemandirian Belajar Siswa SMP dengan Menggunakan Model Investigasi Kelompok - Nova Fahradina; Bansu Irianto Ansari; Saiman Saiman (Didaktik Matematika, 2014)
Once of the meaning of mathematic studying is to learn the communication, because the students may provide the ideas to the teacher and other trough. On the other side, the interpersonally studying of the student much concerning to the process and the result of the student learns, because the interpersonally studying might easily solve the problem and act as an adult. Once of the studying model may applicable to increase the mathematically communication ability and the interpersonally studying is the group model investigation. This research aims to know the increasing of mathematically communication ability and the interpersonally studying between students who get group investigation lesson and students who get conventional lesson concerning all generally and based of student level. This research is use the experimental research. The design used of the research is pre-test post-test control group design. The population of the research are all of the students level VII of National 9 Junior High School of Banda Aceh. Random sampling technical used to take the sample. In order to have the data research used the instrument as mathematically communication ability test and interpersonally studying scale form questionary. The result of the research shows that mathematically communication ability and the interpersonally studying student who get group investigation learning are better than students who get conventionally learning as in all generally or even based on student level.